Globalization & Development of Sharia Financial Technology in Indonesia - Syahputra*, Angga; Kaswinata, Kaswinata; Tanjung, Hendri; Rahmani, Nur Ahmadi Bi; Dzuljastri, Dzuljastri (Program Studi Keuangan & Perbankan, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2023)
This research explores the impact of globalization on the development of Sharia Financial Technology (FinTech) in Indonesia. The phenomenon of globalization has spurred the growth of FinTech, including Sharia FinTech, which combines sharia principles with digital technology. This study identifies the factors influencing the growth of Sharia FinTech globally, analyzes its impact on the Muslim community in Indonesia, and explores the challenges and opportunities faced by the industry and financial regulators. This study utilizes descriptive qualitative research method with secondary data sources. The results show that Sharia FinTech has increased the accessibility of financial services in Indonesia, especially for those who were previously unreachable. Innovations in Sharia FinTech products and services create broader financial inclusion and support the growth of the Islamic economy. However, unaligned regulations and licensing complexity are the main challenges. Nonetheless, regulatory harmonization and cooperation between the government, regulators and industry are key steps in optimizing the potential of Islamic FinTech. This research provides insights for policymakers, regulators, and financial industry players to effectively and sustainably manage the development of Islamic FinTech amidst the dynamics of globalization.